The Poetics of Sensational Forms: Azorean Art, Religion, and Popular Culture - Nolasco, Ana (Religion and the arts, 2022)
This article seeks to analyze the drift of elements of Azorean popular religion into the domain of art orchestrated by two Azorean artists, Catarina Branco and Sofia de Medeiros. The change brings unlikely marriages into fruition, uniting the humor of pop art and the solemnity of the arches of the high choir in a church, the spirit of revelry and a sign of the cross, representing the unfathomable—death, the dread of emptiness to the feeling of unity in communitas. The presentation, together with the strangeness of decontextualization provoked by this change, invoke the walk of the visitor, during which different senses are awakened, in which the poetic imagination of the observer is called forth to complete the different meanings. In this thesis I shall argue that the elements of popular religiosity carried by these artists into the domain of art constitute sensory arrangements, in the sense given to this term by Meyer, providing structure to a collective religious experience particular to Azorean culture where the sacred intertwines with the profane. The mediation of the transcendent through these sensory arrangements leads, on one hand, to contamination and reciprocal intensification of the spheres of art and religion and, on the other hand, to a renewed look at the contemporaneous and its connection to the spiritual.